Stable isotope dilution mass spectrometry quantification of hydrogen sulfide and thiols in biological matrices - Malaeb, Hind; Choucair, Ibrahim; Wang, Zeneng; Li, Xinmin S.; Li, Lin; Boyd, W. Christopher; Hine, Christopher; Tang, W.H. Wilson; Gogonea, Valentin; Hazen, Stanley L. (Redox biology, 2022)
Hydrogen sulfide (H2S), a gaseous signaling molecule that impacts multiple physiological processes including aging, is produced via select mammalian enzymes and enteric sulfur-reducing bacteria. H2S research is limited by the lack of an accurate internal standard-containing assay for its quantitation in biological matrices. After synthesizing [34S]H2S and developing sample preparation protocols that avoid sulfide contamination with the addition of thiol-containing standards or reducing reagents, we developed a stable isotope-dilution high performance liquid chromatography tandem-mass spectrometry (LC-MS/MS) method for the simultaneous quantification of Total H2S and other abundant thiols (cysteine, homocysteine, glutathione, glutamylcysteine, cysteinylglycine) in biological matrices, conducted a 20-day analytical validation/normal range study, and then both analyzed circulating Total H2S and thiols in plasma from 400 subjects, and within 20 volunteers before and after antibiotic-induced suppression of gut microbiota. Using the new assay, all analytes showed minimal interference, no carryover, and excellent intra- and inter-day reproducibility (≤7.6%, and ≤12.7%, respectively), linearity (r2 > 0.997), recovery (90.9%–110%) and stability (90.0%–100.5%). Only circulating Total H2S levels showed significant age-associated reductions in both males and females (p < 0.001), and a marked reduction following gut microbiota suppression (mean 33.8 ± 17.7%, p < 0.001), with large variations in gut microbiota contribution among subjects (range 6.0–66.7% reduction with antibiotics). A stable-isotope-dilution LC-MS/MS method is presented for the simultaneous quantification of Total H2S and multiple thiols in biological matrices. We then use this assay panel to show a striking age-related decline and gut microbiota contribution to circulating Total H2S levels in humans. •We describe the first stable isotope dilution LC-MS/MS assay for hydrogen sulfide.•Systemic H2S levels are reduced with aging in both men and women.•Gut microbes significantly contribute H2S levels in subjects.•There is large variation in gut microbiota contribution to H2S levels in subjects. Hydrogen sulfide (H2S), a gaseous molecule with presumed links to aging, is produced by both mammalian cells and sulfur-reducing enteric commensals. Here, [34S]Na2S was synthesized as internal standard and used to develop a stable isotope-labelled liquid-chromatography-tandem-mass spectrometry method for the simultaneous quantification of Total H2S and thiols in biological matrices. Beyond normal range studies, plasma H2S and six abundant thiols were examined in a clinical cohort (n = 400), and in subjects before and after suppression of gut microbiota. Total H2S levels were significantly reduced with aging, and gut microbiota contribution to circulating Total H2S was shown to vary significantly between subjects.